A Method of Measuring the Solubilities of Hydrocarbons in Aqueous Solutions - Brown, Robert L. (J Res Natl Bur Stand A Phys Chem, 1974)
An apparatus is described which measures the equilibrium distribution of a hydrocarbon between a gas phase and a liquid water phase. The method involves a multiple equilibration procedure which requires the analysis of only the gas phase. Gas-liquid chromatography was used for the hydrocarbon analysis because of its high sensitivity and selectivity. Supplemented by vapor pressure data, the observed distribution can be used to calculate the solubility of the hydrocarbon in the liquid phase. This was done for benzene, toluene, and ethylbenzene in distilled water over the temperature range 5 to 20 °C and in an artificial seawater over the temperature range 0 to 20 °C. The various factors affecting the accuracy of the results are discussed in detail.